Pharmacokinetic analysis of topotecan after superselective ophthalmic artery infusion and periocular administration in a porcine mode - Schaiquevich, Paula Susana (2012)
Purpose: To characterize the vitreous and plasma pharmacokinetics of topotecan after ophthalmic artery infusion (OAI) subsequent to superselective artery catheterization and to compare it with periocular injection (POI). Methods: The ophthalmic artery of 4 pigs was catheterized and 1 mg of topotecan infused over a period of 30 minutes. The contralateral eye was subsequently used for administering topotecan by POI. Serial vitreous specimens were obtained by microdialysis and plasma samples collected and assayed for total and lactone topotecan. Results: Maximum total topotecan concentration in the vitreous (median, range) was significantly higher after OAI compared with POI (131.8 ng/mL [112.9–138.7] vs. 13.6 ng/mL [5.5–15.3], respectively; P , 0.005). Median vitreous exposure calculated as area under the curve for total topotecan attained after OAI was significantly higher than after POI (299.8 nghour/mL [247.6–347.2] and 48.9 nghour/mL [11.8–63.4], respectively; P , 0.05). The vitreous to plasma exposure ratio was 29 after OAI and 3.4 after POI. Systemic exposure for total topotecan was low after both modalities of administration, with a trend to be lower after OAI compared with POI (10.6 nghour/mL [6.8–13.4] vs. 18.7 nghour/mL [6.3–21.7]; P = 0.54). Conclusion: Superselective OAI resulted in significantly higher vitreous concentrations and exposure and a trend toward lower systemic exposure than POI.